EXPLORATION OF POSSIBILITY TO INCREASE PERFORMANCE OF METHOD FOR NOISE VARIANCE EVALUATION IN DIGITAL IMAGES - Виктория Валерьевна Абрамова; Сергей Клавдиевич Абрамов; Владимир Васильевич Лукин; Галина Анатольевна Проскура (Радіоелектронні і комп'ютерні системи, 2017)
The method for blind noise variance evaluation based on analysis of distributions of discrete cosine transform coefficients is considered. The possibility to improve computational efficiency of this method by means of decreasing number of processed blocks is explored. Numerical simulation results obtained for large image database have shown that if partly overlapping or non-overlapping blocks are used it is possible to essentially decrease time needed for obtaining noise variance estimates wherein for low- and medium textured images the decreasing of noise variance estimation accuracy is negligible.